Methodology and Implementation of an Architecture for Egocentric Manual Interactivity in Monocular Augmented Reality - Acchetta, Éverton C.; Laheras, Lucas P.; Risch, Helmuth A.; Santos, Vinicius L. O. P.; Rodrigues, Paulo S. (Anais do Workshop de Visão Computacional (WVC); 2021: Anais do XVII Workshop de Visão ComputacionalDO - 10.5753/wvc.2021.18902, 2021)
Investments in Augmented Reality (AR) have grown considerably in recent years. This advance is due to the increased use of AR in areas such as education, training, games and medicine. In addition, technological advances in hardware enable devices that, a few years ago, were unthinkable. A popular example is Microsoft Hololens 2, which allows the user to use their own hands as a means of interacting with an AR experience. However, a disadvantage from this device is its high cost due to several sensors. Thus, this project offers an AR architecture that uses only a monocular RGB camera as a sensor, allowing the user to interact with an AR experience using their hands to perform gestures similar to the Microsoft Hololens 2 architecture, where it is possible to handle a virtual object in the same way that a real object would be manipulated. The results obtained are promising, where the verification of the interaction of the hand with the virtual object worked in approximately 80% of the tests carried out, respecting the path defined by hand movement.